Maximal inhibitory effect of MOV10 on LINE-1 retrotransposition requires both the MOV10/LINE-1 association and granule formation. - Qian Liu; Yaqi Liu; Yang Mao; Dongrong Yi; Quanjie Li; Jiwei Ding; Saisai Guo; Yongxin Zhang; Jing Wang; Jianyuan Zhao; Ling Ma; Xiaozhong Peng; et al. (PLoS Genetics)
LINE-1 is the only active autonomous mobile element in the human, and its mobilization is tightly restricted by the host to maintain genetic stability. We recently reported that human MOV10 recruits DCP2 to decap LINE-1 RNA by liquid-liquid phase separation (LLPS), resulting in the inhibition of LINE-1 retrotransposition, while the detailed mechanism still awaits further exploration. In this report, we found that the extended motif II (563-675aa) and the C-terminal domain (907-1003aa) of MOV10 cooperated to achieve maximal inhibition on LINE-1 retrotransposition. The extended motif II involves the interaction between MOV10 and LINE-1, and the C-terminal domain is required for MOV10's association with G3BP1 and thereby the formation of granules. The association with LINE-1 through the extended motif II is dominantly attributed to MOV10-mediated anti-LINE-1 activity. On this basis, promoting large granules formation by the C-terminal domain warrants maximal inhibition of LINE-1 replication by MOV10. These data together shed light on the detailed mechanism underlying MOV10-mediated inhibition of LINE-1 retrotransposition, and provide further evidence supporting the important role of MOV10-driven granules in the anti-LINE-1 action.